GENESIS AND EVOLUTION OF CONCEPT OF FIGHTING AGAINST SPIRITUL THREATS (Scientific journal of the Fergana State University, 2023)
As a result of the globalization processes, the relationship between countries and peoples has become much deeper, characterized by the information revolution, the rapid development of science and technology. At the same time, ideological threats aimed at capturing the human mind and hearts grow, and mercenary goals are pursued by various currents and forces. Understanding the essence of the concepts of "spirituality", "spiritual threat", "mechanisms of preventing a spiritual threat", etc. Is the requirement of time. The article analyzes data on the essence, origin and gradual development of such concepts. role of sources in covering historical events and processes is invaluable.